Digital Supply Chain Model for Basic Education Core Curriculum Management in Thailand - Artaphon Chansamut (ExcelingTech, 2022)
The paper aimed to study and to evaluate digital supply chain model for Basic Education Core Curriculum management in Thailand. The samples are ten experts in the field of digital ,supply chain and curriculum . The data is analysed by means and standardized deviations. The paper result shows that the model consists of seven elements namely main elements, Suppliers, school , Finished product customers, satisfaction and Return The assessment of model using Black-Box . The paper findings revealed that model is appropriate at the high .The model could be applied in support the tasks.